2005
DOI: 10.1080/10640260590918946
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Prevention Program for Disordered Eating in Adolescent Girls: Examining Responses of High- and Low-Risk Girls

Abstract: A prevention program for disordered eating was evaluated. Grade 9 girls (N = 173) were assigned to a prevention intervention (n = 114) or a no-treatment control group (n = 59). High-risk, but not low-risk, girls reported significant improvements in body dissatisfaction, drive for thinness, and interoceptive awareness at post-intervention. These changes were not maintained at three-month follow-up, although nonsignificant trends were still apparent for high-risk girls. Individual session analyses indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
2
9
0
4
Order By: Relevance
“…Rather they can experience significant improvements in a universal setting, avoiding problems of: stigmatization (Franko, 2001); impracticalities of having some students miss regular lesson time (Wilksch & Wade, 2009b); and, the difficulties associated with accurate identification of all high-risk students given how prevalent disturbed eating attitudes and behaviours are in adolescent populations. More broadly, these findings reinforce our previous conclusions of the program having a long-term benefit (Wilksch & Wade, 2009a) and are more promising than other studies where benefits have not been maintained over much shorter follow-up periods (Weiss & Wertheim, 2005) or where very limited benefits have been found (Stewart, Carter, Drinkwater, Hainsworth, & Fairburn, 2001). …”
Section: Discussionsupporting
confidence: 88%
“…Rather they can experience significant improvements in a universal setting, avoiding problems of: stigmatization (Franko, 2001); impracticalities of having some students miss regular lesson time (Wilksch & Wade, 2009b); and, the difficulties associated with accurate identification of all high-risk students given how prevalent disturbed eating attitudes and behaviours are in adolescent populations. More broadly, these findings reinforce our previous conclusions of the program having a long-term benefit (Wilksch & Wade, 2009a) and are more promising than other studies where benefits have not been maintained over much shorter follow-up periods (Weiss & Wertheim, 2005) or where very limited benefits have been found (Stewart, Carter, Drinkwater, Hainsworth, & Fairburn, 2001). …”
Section: Discussionsupporting
confidence: 88%
“…10,43,[63][64][65][66] Similarly, while some studies have found that an intervention for adolescents had a positive impact on body image, 38,39,64,66 some have failed to find this effect at follow-up, 42,43,67 while others have found no effect. 40,41,44,45,62,65,66,[68][69][70] Also, while some research has found an improvement in eating disorder symptoms, [37][38][39]62,65,71 a number of studies have not. 69,72,73 Furthermore, while an effect on self-esteem has been found, 67 this is unusual.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, only selected interventions prevented future increases in EP observed in control groups, suggesting that the effects did not just result from an initial decrease in eating disturbances. Several universal prevention programs were also more effective for subgroups of high-risk participants than for the full sample [21], [22], [23], [24], [25]. Three studies not included in the meta-analysis, however, found that a dissonance-based program produced similar results for low and high-risk sub-groups [26], [27], [28].…”
Section: Features Of Successful Ed Prevention Programsmentioning
confidence: 99%